LACK OF INTEREST IN CHILDREN SONGS ON ELEMENTARY SCHOOL STUDENTS - Hery Supiarza; Nada Sofia Irmanika; Yudi Sukmayadi (JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
Abstract. This article illustrates how students' interest in children's songs and adult songs and what factors influence students' lack of interest in children's songs. The method used in this study is descriptive method through a quantitative approach by conducting a survey directly into the field for students of 5th-B-grade Isola 195 Elementary School, amounting to 29 students and the technique of collecting data using a questionnaire instrument in the form of a check list. The results of data analysis were 74.5% of students preferred adult songs and 25.5% of students did not like adult songs and as many as 60% of students liked children's songs and 40% of students did not like children's songs. This shows that students 'interest in children's songs is lower than students' interest in adult songs. This is influenced by several factors, namely family environment factors consisting of parents and other family members, school environment factors consisting of teachers and school friends as well as factors from themselves. Keywords: interests, children's songs, factors